2007
DOI: 10.1111/j.1525-1470.2007.00549.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cyclosporin Plus Topical Corticosteroid Therapy Diminishes Bone Mass in Children with Eczema

Abstract: Topical corticosteroids remain the most common treatment for eczema; however, it is uncertain whether long-term use of these agents has any adverse effect on bone mass. Cyclosporin is very useful in patients with severe atopic dermatitis who have failed conventional therapy. It has been shown to induce bone loss. We compared 43 children with severe eczema who were using topical corticosteroids with 73 healthy children. Of the 43 patients, six were also taking cyclosporin. Bone mineral density was measured in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 53 publications
0
34
0
2
Order By: Relevance
“…86 Cyclosporine has been used for children with dermatologic disorders, such as atopic dermatitis, psoriasis, Henoch-Schönlein purpura, and polymyositis-dermatomyositis, at doses from 3 to 10 mg/kg/d. 84,[87][88][89] The spectrum of side effects is similar to that seen in adults. Recently, it was reported that patients with eczema on topical corticosteroids and cyclosporine had lower lumbar spine bone mineral apparent densities compared with those on only topical corticosteroids.…”
Section: Cyclosporine For Pediatric Patients With Psoriasismentioning
confidence: 73%
See 2 more Smart Citations
“…86 Cyclosporine has been used for children with dermatologic disorders, such as atopic dermatitis, psoriasis, Henoch-Schönlein purpura, and polymyositis-dermatomyositis, at doses from 3 to 10 mg/kg/d. 84,[87][88][89] The spectrum of side effects is similar to that seen in adults. Recently, it was reported that patients with eczema on topical corticosteroids and cyclosporine had lower lumbar spine bone mineral apparent densities compared with those on only topical corticosteroids.…”
Section: Cyclosporine For Pediatric Patients With Psoriasismentioning
confidence: 73%
“…The authors suggest that this may lead to a modest increase in the risk of wrist and forearm fractures in children using cyclosporine. 89 …”
Section: Cyclosporine For Pediatric Patients With Psoriasismentioning
confidence: 97%
See 1 more Smart Citation
“…33 In childhood eczema, patients with severe disease treated with topical corticosteroids and cyclosporin had much lower BMD as measured by dual energy X-ray absorptiometry (DEXA) than those prescribed topical corticosteroids alone. 34 The BMD was similar between Dutch children with moderate-to-severe eczema and the general population. 35 Overall, there are limited data regarding BMD in childhood eczema.…”
Section: Discussionmentioning
confidence: 88%
“…Pedreira et al 8 also found a decreased BMD in children with moderate to severe AD, associated with the use of cyclosporine (n = 6). Comparison with our data is difficult because children using inhalation or oral corticosteroids at inclusion were excluded and data on the use of these drugs in the past were not given in the study of Pedreira et al 8 Furthermore, the authors did not express BMD in Z-scores. A limitation in our study is that the number of children using additional systemic treatment is low.…”
Section: Discussionmentioning
confidence: 92%